PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP PRODUKTIVITAS KERJA APARATUR PADA KANTOR BUPATI MINAHASA SELATAN - Rembang, Meiske M. (HOLISTIK, Journal Of Social and Culture, 2011)
The objective of implementing decentralization in Indonesia government system offering autonomy to local government is to minimize the gap between the government as policy maker of the development and society as the object of development. The decentralized policy and regional autonomy which was implemented recently was aimed to overcome problems in centralized development with the expectation that development policy was formulated for more oriented on the society needs and importance. Results of this study showed development of human resources have a great influence on productivity of staff Therefore development of resources can be made as one potential factor that was observed in this study showed to improve the tin ding for example the formal education, training the government officers have become a measurement to know his work ability.From this study it can be concluded that development of human resources in Kabupaten Minahasa Selatan can be categorized as "good". Work productivity of staff can be categorized as good as indicated by applying of efficiency in performing tasks. Keywords : human resource, development, government